PROFIL INTERAKSI SOSIAL SISWA DAN IMPLIKASI BAGI BIMBINGAN PRIBADI SOSIAL - Noer Moch Adam; Evi Afiati; Bangun Yoga Wibowo (Jurnal Penelitian Bimbingan dan Konseling, 2023)
The phenomenon that happen in the school environment was related to the social interaction process of students, including students who found it difficult to work with students who are not part of the play group. Thus, there will be students who are isolated in the class. During the teaching and learning process, students found it difficult to express their opinions in front of the class, and It was found that students often belittled and ridiculed their peers. The aims of this study was to obtain an overview of students 'social interactions and to design personal social guidance and counseling programs to develop students' social interactions. This type of research was descriptive research. Sampling was done by total sampling technique, in which all populations were sampled. The total of the ample was 49 grade VII students of SMP Negeri 4 Saketi. Research on student social interaction can be seen from 2 indicators, namely associative and dissociative. The data collection technique used was in the form of distributing the research instrument in the form of a questionnaire. The data analysis technique used quantitative descriptive techniques. The results showed that the level of social interaction of class VII students of SMP Negeri 4 Saketi was in the medium category of 65.3%, the high category was 20.4%, and 14.3% in the low category. After knowing the description of students' social interactions, then design of the program can be made based on the research results that have been obtained.Keyword: Social Interaction, Social Personal Guidance and Counseling